Survey of software defined D2D and V2X communication - Wenjuan SHAO; Qingguo SHEN (Tongxin xuebao)
The related D2D (device-to-device) and V2X (vehicle-to-everything) are regarded as vital components of 5G communication system,which providing alternative network services and multiple application services for cellular network.In the meanwhile,SDN (software defined networking) can improve the compatibilities and flexibilities of D2D and V2X.SD-D2D (software defined D2D communication) and SD-V2X (software defined V2X communication) technologies were reviewed.Based on their similarities and respective characteristics,their state-of-arts and architectures were reviewed accordingly,and the key technologies such as D2D location/discovery management,D2D routing control,D2D flow table management,V2V path scheduling,and V2V path recovery were analyzed.Finally,it was pointed out that the SD-D2D architecture was approaching mature and the SD-V2X framework had been preliminarily determined,the existing problems of interference management,mobile management and routing management in D2D/V2X communication could be effectively solved.Furthermore,it was also pointed out that the disconnection between the existing SD-D2D/V2X studies and the actual application needed to be overcome.